Online Module to Improve Emergency Department Observation Unit Practice - Sangil Lee; Ian Young; James Colletti (Association of American Medical Colleges, 2016)
Abstract Introduction The emergency department (ED) observation unit has become a unique practice opportunity to liberate inpatient capacity in the United States. Substantial variations in clinical practice and level of comfort among ED providers existed in a large health care system. We aimed to study the effectiveness of an educational module targeted for emergency medicine providers. Methods We developed a 20-minute online module including pretest, learning module, and posttest. The format consisted of Likert-scale (1 = least comfortable, 5 = most comfortable), true-or-false, and multiple-choice questions. The learning module contained slides, script, and figures describing management strategy for commonly encountered conditions in the observation unit. The institutional review board granted exempted review. Pre- and posttest scores were evaluated with the Wilcoxon rank-sum test, and a p value of less than .05 was considered significant. Results Twenty-one participants completed the pretest, with a mean score of 63.8 (SD = 19.3), and 14 participants completed the posttest, with a mean score of 87.9 (SD = 9.7; p = .0001). Eight participants responded to a follow-up survey, a response rate of 57%. Responses demonstrated that levels of provider comfort in selection of observation (M = 4.3, SD = 1.5), choice of stress test for chest pain (M = 4.3, SD = 1.0), asthma management (M = 4.1, SD = 1.0), anaphylaxis care (M = 4.1, SD = 1.4), and documentation (M = 4.3, SD = 0.9) were high. Discussion An online learning module can be useful to enhance the knowledge of observation medicine among emergency medicine providers.